2018
DOI: 10.1007/s12223-018-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

KH-type splicing regulatory protein is regulated by nuclear factor-κB signaling to mediate innate immunity in Caco-2 cells infected by Salmonella enteritidis

Abstract: Salmonella enteritidis infection occurs in enterogenous diseases, such as gastroenteritis and parenteral focal infection, which often involve inflammation of intestinal epithelial cells. The nuclear factor kappa B (NF-κB) pathway participates in the innate immune response to many gram-negative pathogenic bacteria and initiates inflammation in epithelial cells. KH-type splicing regulatory protein (KSRP) is a multi-domain RNA-binding protein that recruits the exosome-containing mRNA degradation complex to mRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Pro-inflammatory cytokines such as TNF-α, interferon-γ, and IL-1β have been recognized to contribute to intestinal barrier dysfunction and exacerbate inflammatory responses, while anti-inflammatory cytokines (IL-10 and TGF-β) have been reported to be positively associated with intestinal barrier tissue repair during the course of inflammatory bowel disease [30]. In this study, the interaction of SE with intestinal epithelial cells induced obvious inflammatory responses in Caco-2 cells, as proven by up-regulating pro-inflammatory cytokines (IL-1β, IL-8, and TNF-α), which was consistent with the results of previous studies [31][32][33][34]. Interestingly, SE boosted IL-10 mRNA levels but decreased IL-10 protein levels.…”
Section: Discussionsupporting
confidence: 93%
“…Pro-inflammatory cytokines such as TNF-α, interferon-γ, and IL-1β have been recognized to contribute to intestinal barrier dysfunction and exacerbate inflammatory responses, while anti-inflammatory cytokines (IL-10 and TGF-β) have been reported to be positively associated with intestinal barrier tissue repair during the course of inflammatory bowel disease [30]. In this study, the interaction of SE with intestinal epithelial cells induced obvious inflammatory responses in Caco-2 cells, as proven by up-regulating pro-inflammatory cytokines (IL-1β, IL-8, and TNF-α), which was consistent with the results of previous studies [31][32][33][34]. Interestingly, SE boosted IL-10 mRNA levels but decreased IL-10 protein levels.…”
Section: Discussionsupporting
confidence: 93%
“…To date, however, the molecular mechanisms by which KHSRP promotes lung cancer cell migration and invasion have not been elucidated. Previous studies have reported that activation of the KHSRP-mediated nuclear factor-κB, PI3K/AKT or p38 signaling pathway is closely associated with lung tumorigenesis and metastasis [16, 40, 41]. However, the detailed regulatory mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could help in cell cycle arrest and initiate the programmed cell death by downregulating the NF-kB genes. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][45][46][47][48][49][50] Curcumin reduces the iNOS i.e. inducible nitric oxide synthase which is concerned with oxidative stress and ROS generation through activation of neutrophils and macrophages.…”
Section: Curcuminmentioning
confidence: 99%
“…47 Thus, Curcumin can stop cancer either by blocking the growth of cancer cells or by putting a halt on its invasion as shown inFigure 3. 47,48,[50][51][52][53][54][55][56] The structural activity relationship studies showed that substitution of ortho-methoxy group and hydrogenation of heptadiene group, both are responsible for scavenging of radicals 57,58 to give an antioxidant effect whereas less hydrogenation of the unsaturated diketone moiety and methoxylation of the molecules are highly responsible for the anti-inflammatory and anti-tumoral effect. 43 Further advanced studies showed that the presence of aromatic rings is important for cytotoxic and antiandrogenic activity along 59 with substitutions of 3´-dimethoxy and 4´dimethoxy and/or 3´-methoxy-4´-hydroxy substitutions on phenyl ring which will help in designing new Curcumin analogs.…”
Section: Curcuminmentioning
confidence: 99%